Feeding performance of stabulated dairy cows consuming integral diets of tropical forages - Reyes, Julio J.; G?lvez, M.; Noda, Aida; Redilla, Carmen (Cuban Journal of Agricultural Science, 2013)
In order to characterize the performance of dairy cows under stabulation conditions, fed integral diets of tropical forages, a study was conducted for three years. The observations were conducted for 72 h consecutively in each season to calculate the times spent in each activity (feed intake, rumination, water ingestion, resting and walking). A linear model of fixed effect was used for the statistical analysis, controlling group, season, year and possible interactions. The times dedicated to consumption were longer (P < 0.01) during the day and in the dry season (369.47, 83.67, 415.55 and 120.40 min, rainy/daytime, rainy/night time, dry season/daytime and dry season/night time, respectively). In rumia, the times increased (P < 0.001) in the dry season and at night (67.35, 271.79, 61.23 and 329.07 min for rainy/daytime, rainy/night time, dry season/daytime and dry season/night time, respectively). The intake rate of the milking cows in both seasons diminished (P < 0.01) in 24.2 and 25.5 % in the rainy and dry season, respectively, compared with those that were not lactating. The distribution of the animals? percentage in the intake activity was maintained, approximately, in 90.0 % in the rainy season, three hours after the feed supply, and in the dry season during the first five hours. Meanwhile, the animals? percentage in rumination was concentrated between 10.00 p.m. and 3.00 a.m., and was superior to 40 %. The study demonstrated that, apart from the management under stabulation conditions, the animals maintained a behavior in accordance with the availability and quality of forages. Besides, it was proved that the feed supply time influences markedly on the intake distribution. Key words: intake, rumination, forages, stabulation, schedule.